Detection of Spodoptera exigua (Hübner) Larval Infestation on Leeks and Shallots: A Case Study in North Tapanuli and Karo, North Sumatra, Indonesia - Ameilia Zuliyanti Siregar; Suputa Suputa; Lindung Tri Puspasari; Abdul Hafiz Ab. Majid (Journal of Applied Agricultural Science and Technology, 2026)
North Sumatra Province is the eighth largest producer of shallots (Allium cepa) in Indonesia (1.09%, 53,962 tons). Declining shallot production is primarily caused by attacks by pests and pathogens, which are responsible for 20–100% decreases in yields. Spodoptera exigua larvae are among pests with significant effects on shallot productivity. This study aimed to determine the effectiveness of various methods of monitoring Spodoptera exigua infestation on shallots, particularly of the Batu Ijo and Brebes varieties, including the use of yellow sticky traps, blue ball traps, sweep nets, and hand-picking, for the purpose of increasing farmers' income in North Tapanuli and Karo, Sumatra Utara. The research was conducted in Parhorboan Village, Pagaran Sub-district, North Tapanuli Regency, and Juhar Sub-district, Karo Regency, North Sumatra, from June to July 2024. To be precise, it was conducted in three farmers' planting areas, using the diagonal slice method with five sub-plots and observations with one-week intervals at the sampling locations. The results showed that the infestation by S. exigua larvae was higher on shallots than on leeks. The highest average number of larvae recorded on leeks was 0.78 larva per plant, while shallots had an average of 1.84 larvae per plant. Furthermore, the highest average percentage of S. exigua larval infestation on leeks was 16.78%, while the infestation on shallots reached 32.15%. The intensity of S. exigua infestation fell within the 3–5 categories, which correspond to medium to very high levels. The independent sample t-test results showed significant differences in both the population and infestation percentage of S. exigua larvae in the leek and shallot planting areas.